2018
DOI: 10.1371/journal.pone.0193299
|View full text |Cite
|
Sign up to set email alerts
|

Reduced NK cell IFN-γ secretion and psychological stress are independently associated with herpes zoster

Abstract: The pathogenesis of herpes zoster is closely linked to reduced varicella-zoster virus-specific cell-mediated immunity. However, little is known about the interplay between natural killer cells and psychological stress in the pathogenesis of herpes zoster. This study aimed to investigate possible associations among natural killer cells, T cells and psychological stress in herpes zoster. Interferon-gamma secretion from natural killer cell, psychological stress events, stress cognition scale scores and cytomegalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
2
10
0
2
Order By: Relevance
“…Additionally, after 2 days of co-culture, VZV exposed NK cells also exhibited suppressed cytokine production, suggesting VZV can affect the efficiency of cytokine expression through several regulatory or inhibitory methods. Recently it was found that NK cells isolated from patients with herpes zoster exhibited significantly lower IFN-γ secretion compared to control subjects, with severity of skin lesion correlated to the degree of IFN-γ suppression [40], corroborating our findings. Reduced IFN-γ and TNF expression upon PMA/I stimulation indicates that VZV and HSV-1 impact points in the cytokine production pathway that are not shared with degranulation, which was unaffected following activation with PMA/I.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, after 2 days of co-culture, VZV exposed NK cells also exhibited suppressed cytokine production, suggesting VZV can affect the efficiency of cytokine expression through several regulatory or inhibitory methods. Recently it was found that NK cells isolated from patients with herpes zoster exhibited significantly lower IFN-γ secretion compared to control subjects, with severity of skin lesion correlated to the degree of IFN-γ suppression [40], corroborating our findings. Reduced IFN-γ and TNF expression upon PMA/I stimulation indicates that VZV and HSV-1 impact points in the cytokine production pathway that are not shared with degranulation, which was unaffected following activation with PMA/I.…”
Section: Discussionsupporting
confidence: 89%
“…Given that these patients had advanced disease and were heavily pre-treated, infectious complications could reflect a combination of decreased innate responses and dysfunctional humoral and cell-mediated immunity, already present in these patients. It is well known that NK cells contribute to the defense against herpesviruses, including CMV, HSV-1 and VZV [27,3639]. NK cells can detect virus infection directly by recognition of viral proteins, and indirectly by binding to molecules that are up-regulated on stressed cells.…”
Section: Discussionmentioning
confidence: 99%
“…Infliximab downregulated interferon (IFN)‐γ activation by 5.9‐fold but none were evident for etanercept. Since IFN‐γ is a critical factor for enhancement of natural killer activity and inhibition of VZV replication, it was postulated that defective IFN‐γ production may be related to VZV reactivation . Pharmacokinetic differences also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Since IFN-γ is a critical factor for enhancement of natural killer activity and inhibition of VZV replication, 30 it was postulated that defective IFN-γ production may be related to VZV reactivation. 31,32 Pharmacokinetic differences also play a role. According to the therapeutic window concept, 33 the steady-state range of serum or tissue drug concentrations should be adequate to neutralize surplus TNF, yet not so high as to threaten host defense.…”
Section: Discussionmentioning
confidence: 99%